IMPLEMENTATION OF PANCASILA VALUES IN ALTERNATIVE DISPUTE RESOLUTION IN THE FORM OF NEGOTIATIONS - Rohaini, Rohaini; Putri, Ria Wierma; Andini, Pingkan Retno (Sriwijaya Crimen and Legal Studies, 2024)
Courts that accommodate dispute resolution are still not optimal in implementing fair decisions for the parties. Not only has it not created justice, but it has not been able to resolve the dispute quickly. In the end, there was a backlog of cases, so the simple, fast, low-cost justice principle was difficult to realize. Alternative Dispute Resolution is one of the efforts that can be implemented to assist the court in reducing the number of cases piling up, one of which is in the form of negotiations as regulated in Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. In principle, negotiations are concerned with implementing the Principle of Deliberation and Consensus as implied in the Preamble to the 1945 Constitution as stipulated in the Alternative Dispute Resolution Act. The problematic legal issues in its implementation are compiled in this article, analyzing the weaknesses of Negotiation as an Alternative for Resolving Business Law Disputes in Indonesia as well as the context for the Implementation of Pancasila Values. The type of research used is normative juridical with descriptive research type. The results that will be discussed explain the technical weaknesses of Alternative Dispute Resolution through Negotiations, which are generally linked to business law events in Indonesia in applying Pancasila values, especially the values of Humanity and Deliberation to Consensus. This writing concludes that Alternative Dispute Resolution must continue to be pursued in resolving disputes and in minimizing the weaknesses of the process, including opinions are submitted systematically, politely, and creatively, looking for common ground wisely, viewing the other party as family to create a family atmosphere, and accommodating Pancasila values as a guide to implementing written law.